Aging mechanism of MoS2 nanosheets confined in N-doped mesoporous carbon spheres for sodium-ion batteries. (August 2019) - Hou, Mingzhen; Qiu, Yongting; Yan, Guanfusheng; Wang, Jinming; Zhan, Da; Liu, Xiang; Gao, Jingchang; Lai, Linfei
Abstract: N -doped hollow carbon nanospheres (NHCS) with mesoporous carbon shells is selected as nanoreactors and encapsulated with few-layered MoS2 nanosheets to monitor its electrochemical properties and structural conversion in long-term cycling. Mesoporous walls of NHCS can facilitate electrolyte penetration and provide conductive shells for superior mass diffusion and charge transfer. When serving as SIB anodes, MoS2 @NHCS has a capacity value of 371 mAh g -1 at 1 A g -1 with a capacity retention of 94.9% after 100 cycles which is higher than powder form MoS2 and is among the highest values of earlier reported MoS2 electrodes. The origin of gradual capacity decay of MoS2 @NHCS anodes in-between 50 to 150 cycles has been investigated. Transmission electron microscopy and ex-situ X-ray diffraction have shown significant morphology change of space-confined MoS2 and the production of MoO3 together with oxygen-deficient MoOx after continuous charge/discharge test. After long-term cycle test of MoS2 @NHCS, the ratios of Mo 6+ and Mo 5+ increased significantly with the decreasing of Mo 4+ ratio, while the sulfur from MoS2 transformed from S 2− to SO4 2− . This work highlight the phase transformation and composition change of MoS2 for MoS2 -based anode in long-duration charge/discharge tests. Graphical abstract: Image 1 Highlights: Few-layered MoS2 nanosheets spaced-confined in N -doped hollow carbon nanospheres (NHCS) as sodium-ion battery anodes. MoS2 @NHCS has a capacity value of 371 mAh g -1 at 1 A g -1 with a capacity retention of 94.9% after 100 cycles. The sodiation of MoS2 nanosheets created irreversible phase and composition change with sodiation mechanism in long-term cycling proposed. After long-term cycling, the ratios of Mo 6+ and Mo 5+ of MoS2 @NHCS increased significantly with the decreasing of Mo 4+ ratio.